Предмет:
Другие предметыАвтор:
анонимПусть наименьшее из чисел равен n, тогда среднее равен (n + 1), а большее число - (n + 2).
n * (n + 1) * (n + 2) + (n + 1) = n * (n2 + n + 2 * n + 2) + n + 1 =
= n * (n2 + 3 * n + 2) + n + 1 = n3 + 3 * n2 + 2 * n + n + 1 = n3 + 3 * n2 + 3 * n + 1 =
= (n + 1)3.
Автор:
french fryxuapДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть